Between Addiction and Privacy: The Phenomenon of Surveillance Capitalism, Internet Addiction, and Privacy Violations among Internet Users in Indonesia - Amrudhia, Nada Farah; Andre Noevi Rahmanto; Ign. Agung Satyawan (Journal of Social Interactions and Humanities, 2024)
This paper focuses on describing the phenomenon of surveillance capitalism which is closely related to internet addiction and privacy violations in Indonesia. In communication perspective, internet addiction is closely related to the Media Dependency theory, and privacy violations are closely related to the Communication Privacy Management Theory. Using the literature review method, this article finds that the majority of Indonesian people are addicted to the internet, which has an impact on social dysfunction behavior, hyperpersonal tendencies, avoiding responsibilities, can not meet targets and feeling anxious. Then, related to surveillance capitalism and privacy violation, the social consequences are not only loss of privacy, but also discrimination, social sorting and data commodification.